Plant-mediated gold nanoparticles in cancer therapy: exploring anti-cancer mechanisms, drug delivery applications, and future prospects - Nisha,; Sachan, Rohan Samir Kumar; Singh, Anjuvan; Karnwal, Arun; Shidiki, Amrullah; Kumar, Gaurav (Frontiers in Nanotechnology, 2024)
Gold nanoparticles (AuNPs) exhibit great promise in cancer therapy and drug delivery due to their unique physicochemical properties. The utilization of plant extracts and phytochemicals for the synthesis of AuNPs offers a simple, rapid, eco-friendly, and cost-effective alternative. This review provides an in-depth analysis of the role of plant-mediated AuNPs in cancer treatment, focusing on their core mechanisms, drug delivery applications, and future potential. It emphasizes the advantages of green synthesis methods for cancer therapy, detailing the processes involved and highlighting various plants used for nanoparticle biosynthesis. The review also explores the anti-cancer effects of plant-mediated AuNPs, such as their ability to selectively target cancer cells and induce apoptosis, supported by both in vitro and in vivo studies. Additionally, the application of these nanoparticles in targeted drug delivery for cancer therapy is examined. The review addresses biocompatibility and toxicity concerns, providing insights into the safety of these nanoparticles. Future research directions and challenges are discussed to overcome current limitations and maximize their clinical applicability.In summary, plant-mediated AuNPs offer a sustainable and effective approach for cancer therapy and drug delivery, with their green synthesis and diverse anti-cancer properties highlighting their potential.Further research is essential to fully realize their clinical benefits.